Study on Control of CSTR Using Intelligent Strategies - mousa, Khalid M.; Dawood, Zainab Essaim (Nahrain University College of Engineering Journal, 2017)
A non linearity, interaction and complexity in modeling lead to a great difficulties in CSTR control system, this paper interested in CSTR control using PID, fuzzy logic and intelligent control strategies. Water flow rate and ethyl acetate were selected as manipulated variables while sodium acetate and reactor temperature as controlled variables. Firstly the system identification was conducted and the results show that the multi input multi output system can be represented by the following matrixThe compare among the strategies show preference of fuzzy control.